Beatrix Potter : Artist, Conservationist, Pioneer - Woolley, Katie; Hsu, Ginnie (London : Puffin Books, 2022)
His stylish mini-hardback takes readers on a fascinating journey through Beatrix's life, from her childhood holidays and animal friends through to her publishing success and later life in the Lake District. More than a children's author, explore Beatrix Potter's vital work as a conservationist and the inspiration she found in the countryside, as well as her artistic talents
Keywords: Potter, Beatrix, -- 1866-1943 -- Juvenile literature; Authors, English -- Juvenile literature -- Biography -- 20th century; Women -- Biography